(untitled) (Alternautas, 2014)
Are there currently more alternative projects of and to development ongoing in the Latin American region? Others than, for example, Buen Vivir (Ecuador)/Vivir Bien (Bolivia), self-governance, participatory budgeting and a general political rupture through the appearance of, what de la Cadena has called, “Earth-beings” (2010)? In this article, I trace another legal-technical, yet humanist, approach to improve people lives in the region; one that has been termed as ’Development 2.0’. This label points at the fusion of two overlapping, yet partly contradicting businesses and movements: social and econ sciences-related development, on the one hand, and legal and technical human rights, on the other (de Béco, 2014). While for a long time both were promoted somehow separately – by different actors and through different institutions (what de Béco has characterized as rather strictly ‘norm-related’ in the case of human rights and more flexible ‘change-related’ in the case of development) – recent advances and ongoing debates regards post-2015 Millennium Development Goals (MDG) have spurred initiatives toward mutually more integral approaches (e.g. Raza and Baxewanos, 2013).